Análise de preços e margens de comercialização de lagosta no estado do Ceará - Cauby de Medeiros Freire, José; Paniago, Euter; Ribon, Miguel; Brandt, Sérgio Alberto (Revista Ceres, 2025)
In spite of efforts to renew resources, the lobster may become extinct if harvest levels rise above increases in the lobster population as determined by the conditions of the physical habitat. ‘The present work, using information from the State of Ceará, attempts to aid decision-makers with respect to planning and the allocation of available resources with the objective of raising efficiency levels of commercial lobster production.